Inicjatywy ziemian i przemysłowców ziemiańskich w wybranych sektorach gospodarki Królestwa Polskiego w drugiej połowie XIX i na początku XX w. - Kowalczyk, Rafał Wiktor (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Landowners were mostly actively engaged in the agricultural and food industries related to modernization of their estates and for which they participated in all aspects of this industry. They were involved, however, in the only manufacturing industrial branch of the agricultural and food industry – i.e. sugar-making. However, their factories were of a mainly agricultural character and of rather small size. These included: distilleries, dairies, potato dryers etc. Landowners occupied themselves only in new businesses related to agricultural production. They did not want to invest in companies connected with the production of products such as candies, chocolate, cakes or pasta that were found mainly in towns and industrial areas. Landowners also got engaged in businesses not connected with farming. Investment of landowners’ capital was considerable in the mineral industry. In most cases these were brickyards which did not demand considerable investments and were located within their estates. Landowners were also involved in coal mining. These investments were rather temporary in nature as they were capital-consuming, risky and demanded long term expenditures. Landowners also invested in ironore mining, mainly in the Świętokrzyski Industrial District. This business was not very capital-consuming with extruded iron-ore being sold off to local steelworks. In 1897, out of 79.63% of mined iron-ore, 32.69% belonged to landowners. In 1913 it was only 7.83% out of 35.93% of mined iron-ore. Landowners who became industrialists were very rare. They included for example: Juliusz Tarnowski, the owner of Końskie Wielkie Factory and Stanisław Ciechanowski, the owner of many lands, mines (“Maria”, “Barbara”, “Walerya”, “Władyslaw”, “Grodziec”), cement works (“Grodziec” located in Grodziec near Będzin). These two people were connected to German investment Joint-stock Company Puszkin Steel-works and Milowizer Eisenwerk A.G., affiliate of upper Silesian Friedenwshütte, one of the part of concern Oberschlesische Eisenbahn-Bedarfs A.G. (Oberbedarf). Landowners were also often engaged in many initiatives aiming at development of the region. They initiated different kinds of projects concerning such areas as building railways (both narrow-gauged and broad-gauged) mainly in agricultural regions such as Kujawy, Lubelszczyzna, areas north of Warsaw (gubernia płocka) and many others. As a result landowners were engaged in many sectors of the economy and not only in industry. They did not invest much capital and the capital they withdrew was spent on the modernization of their farms, estates.